Grade VIII Students’ Understanding of Types of News Texts Reviewed from the Results of Newspaper Identification - Fatimah, Putri Nurul; Markhamah, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The purpose of this study is to describe the types of news texts that can be identified by grade VIII A students from newspapers in the context of learning Indonesian. Methodology: This research uses a qualitative descriptive approach with data collected through documentation. The data source is the identification of newspaper news text types by grade VIII A students. The data analysis process follows three stages: data reduction, data presentation, and conclusion drawing. Results: The study revealed that grade VIII A students successfully identified five types of news texts: (1) direct news texts, (2) in-depth news texts, (3) investigative news texts, (4) interpretive news texts, and (5) opinion news texts. Among these, the most frequently identified type was direct news, comprising 35% of the total. Opinion and interpretive texts each accounted for 21%, investigative texts 14%, and in-depth news texts 7%. Direct news texts were most dominant due to their accessibility, clarity, and relevance to real-life events. Applications/Originality/Value: This study provides insight into students' comprehension of different types of news texts and emphasizes the effectiveness of using newspapers as a learning medium in Indonesian language instruction. It highlights how textual characteristics influence students' ability to recognize various news formats, which can be useful for designing future learning materials and strategies.